2019
DOI: 10.1007/978-3-030-30446-1_16
|View full text |Cite
|
Sign up to set email alerts
|

Towards Logical Specification of Statistical Machine Learning

Abstract: We introduce a logical approach to formalizing statistical properties of machine learning. Specifically, we propose a formal model for statistical classification based on a Kripke model, and formalize various notions of classification performance, robustness, and fairness of classifiers by using epistemic logic. Then we show some relationships among properties of classifiers and those between classification performance and robustness, which suggests robustness-related properties that have not been formalized i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…By using StatEL we introduced (α, n)-statistical secrecy with a significance level α and a sample size n, and showed that StatEL is useful to formalize hypothesis testing and differential privacy in a simple way. As shown in [24], StatEL can also express certain properties of statistical machine learning.…”
Section: Discussionmentioning
confidence: 99%
“…By using StatEL we introduced (α, n)-statistical secrecy with a significance level α and a sample size n, and showed that StatEL is useful to formalize hypothesis testing and differential privacy in a simple way. As shown in [24], StatEL can also express certain properties of statistical machine learning.…”
Section: Discussionmentioning
confidence: 99%
“…Be that as it may, the work of Kawamoto (2019) leads to an account where fairness can be expressed as a logical property using predicates for protected attributes, remarkably similar in spirit to our approach if one were to ignore actions. This should, in the very least, suggest that such attempts are very promising, and for the future, it would be worthwhile to conduct a deeper investigation on how these formalization attempts can be synthesized to obtain a general probabilistic logical account that combines the strength of dynamic epistemic languages and statistical measures.…”
Section: Contributionsmentioning
confidence: 94%
“…It is conducted at goal level without touching concrete functions of ML systems. In [11], a logical approach is given for specifying statistical properties of ML systems based on a Kripke model. It includes formal notations for robustness and fairness of classifiers, as well as relations among properties of classifiers.…”
Section: Related Workmentioning
confidence: 99%